Genre Features and Types of Adyghe Toponymic Legends - Z. Zh. Kudaeva; L. S. Khagozheeva (Научный диалог, 2020)
The article examines the Adyghe toponymic traditions. The relevance of the work is that it addresses one of the complex theoretical problems of modern Russian folklore — the definition of differentiating genre features of works of oral folk prose. The authors proceed from the fact that the identification of genre characteristics of Adyghe toponymic legends should contribute to the creation of a generalizing genre system of Adyghe folk non-fairy prose. The novelty of the research consists in determining the genre features of Adyghe toponymic legends and their classification. In the continuum of Adyghe toponymic traditions, two groups are distinguished: the traditions of the first group are archaic, they tell about the events of the distant past and are known throughout the entire ethnic territory. It is shown that the plot of this type of legend is expanded, complicated and includes a number of additional motives — the history of migration and settlement of the current territories by the people, genealogical excursions. It is noted that another group of toponymic legends is associated with events of the recent past and has a narrow local connectedness. The marker of historical authenticity of the described facts and events is an indication of real historical persons who act as characters in the legend. It is argued that the plot of this type of legend is not developed, they are usually one-episode, and the area of distribution of this group of legends is usually limited to one locality.